Sprawl : a compact history - Bruegmann, Robert (University of Chicago Press, 2005)
As anyone who has flown into Los Angeles at dusk or Houston at midday knows, urban areas today defy traditional notions of what a city is. Our old definitions of urban, suburban, and rural fail to capture the complexity of these vast regions with their superhighways, subdivisions, industrial areas, office parks, and resort areas pushing far out into the countryside. Detractors call it sprawl and assert that it is economically inefficient, socially inequitable, environmentally irresponsible, and aesthetically ugly. Robert Bruegmann calls it a logical consequence of economic growth and the democ.